Predictors of eating behavior disorder in adolescent girls and the mediational effects of body image - Chin, Yit Siew (2009)
Negative body image and eating behavior disorder are serious nutritional issues that should be duly addressed during adolescence to prevent future adverse adult health outcomes. This study aimed to determine the contribution of biological (age, body, mass index, ethnicity, and puberty development), psychological (self-esteem, depressive symptoms) and sociocultural factors (gender-role types, parental influence, peer influence, media influence, social comparison, and thin-ideal internalization) in predicting negative body image between the predictors and eating behavior disorder. Also, the meditational effects of body image and eating behavior disorder were determined for developing a comprehensive multifaceted model of the etiology of eating behavior disorder in adolescent girls. Data for the study were collected from 407 female secondary school students in the Kuantan district, Pahang by using a set of standardized self0administered questionnaire that comprised 11 section, including socio-demographic background, food consumption habits, eating behaviors, body image, sociocultural influences (parents, peers and media), pubertal development, self-esteem, depressive symptoms, types of gender role, thin-ideal internalization, and social comparison. Indeed, two of the instruments in the questionnaire – Multidimensional Body Image Scale (MBIS) and sociocultural Influences on Body Image Scale(SIBIS) were developed to determine the various dimensions of body image and sociocultural influences (parent, peer and media) on body image respectively. Results of factor analysis for the two instrument showed that the MBIS comprised seven dimensions, and the SIBIS consisted of 5-dimension of parental influence subscale, 4- dimension of peer influences subscale, and 3-dimension of media influence subscale. Three models were developed to determine the contributions of the biopsychosocial predictors on i) negative body image, ii) eating behavior disorder (without body image), and iii) eating behavior disorder (with body image). For the negative body image model, six biopsychosocial predictors, namely BMI, depressive symptoms, thin-ideal internalization, media influence, social comparison, and parental influence explained 60.5% of the variances in the model. Further , six of the biopsychosocial predictors, including BMI, Ethnicity, depressive symptoms, social comparison, parental influence, and media influence, were found to explain 29.4% of the variances in the eating behavior disorder (without body image) model. When body image was included in the eating behavior disorder model, two of the biopsychosocial predictors (parental and media influences) dropped out< but body image emerged as one of the biggest contributors, and the variance explained improved to 40.7% for the eating behavior disorder (with Body image) model. The mediation analysis also showed that body image was a mediator in the eating behavior disorder model in which the biopsychosocial predictors were correlated with eating behavior disorder directly and/or indirectly through body image. In summary, the biopsychosocial factors were found to predict negative body image and eating behavior disorder model by mediating the correlation between biopsychosocial predictors and eating behavior disorder. Therefore, efforts should be taken to build positive body image of adolescent girls to prevent eating behavior disorder. Body image should be integrated as one of the important components of intervention program and policy development regarding adolescent nutrition and health, besides eating behavior and physical activity.